Determination of tolerance in Thanatephorus cucumeris, Trichoderma viride, Gliocladium virens and Rhizobium sp. to fungicides - B. PATEL, S.C. DUBEY and (Indian Phytopathology, 2002)
Five seed-dressing fungicides, viz. Bavistin (carbendazim), Captaf (captan), Topsin - M (thiophanatemethyl), Thiram (tetramethyl thiuram disulphide) and Vitavax (carboxin) were evaluated at five different concentrations against Thanatephorus cucumeris (Rhizoctonia solanit, causal agent of web blight of urd and mung bean, the antagonists Trichoderma viride and Gliocladium virens and Rhizobium sp. Carboxin and Captan were selected for integration with G. virens and carboxin and thiophanate-methyl with T. viride as they inhibited the growth of T. cucumeris significantly but not as inhibitory to antagonists. Rhizobium sp. was found insensitive to these fungicides, therefore, these can also be integrated with Rhizobium sp.